2006
DOI: 10.1097/01.ico.0000183484.85636.b6
|View full text |Cite
|
Sign up to set email alerts
|

Application of Umbilical Cord Serum Eyedrops for the Treatment of Dry Eye Syndrome

Abstract: Umbilical cord serum contains essential tear components, and umbilical cord serum eyedrops are effective and safe for the treatment of severe dry eye syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
5
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 23 publications
4
68
5
4
Order By: Relevance
“…Especially, EGF and TGF-b concentrations in umbilical cord serum are three and two times higher than those in autologous serum, respectively. 10 Although vitamin A concentration in umbilical cord serum is lower than that in peripheral blood serum, it is much higher than in tears and is sufficient to prevent squamous metaplasia. 10,12 Recently, several studies have been reported on the beneficial effect of 20% umbilical cord serum eyedrops in the treatment of dry eye syndrome and persistent epithelial defect of the cornea.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Especially, EGF and TGF-b concentrations in umbilical cord serum are three and two times higher than those in autologous serum, respectively. 10 Although vitamin A concentration in umbilical cord serum is lower than that in peripheral blood serum, it is much higher than in tears and is sufficient to prevent squamous metaplasia. 10,12 Recently, several studies have been reported on the beneficial effect of 20% umbilical cord serum eyedrops in the treatment of dry eye syndrome and persistent epithelial defect of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although vitamin A concentration in umbilical cord serum is lower than that in peripheral blood serum, it is much higher than in tears and is sufficient to prevent squamous metaplasia. 10,12 Recently, several studies have been reported on the beneficial effect of 20% umbilical cord serum eyedrops in the treatment of dry eye syndrome and persistent epithelial defect of the cornea. 10,11,19 Umbilical cord serum led to faster healing of persistent corneal epithelial defects refractory to medical treatment compared to autologous serum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations